Integrating Non-verbal Communication and Verbal Communication for Developing English Communication Skills among Primary School Children - Mazta, Swati; Arora, Dr. Sanjay (Voices of Teachers and Teacher Educators, 2020)
Nonverbal communication (NVC) is a wordless communication. Consciously and unconsciously we make use of NVC in our life. It is a communication of gestures and postures through which we communicate silently. These messages are considered to be more genuine and powerful. NVC is a basic part of communication used in the classroom but it is always ignored by the teachers as they are not aware of its importance. Majority of the population of Himachal Pradesh resides in rural or remote areas. People mostly communicate in mother tongue and Hindi and sschool teachers teach English through the grammar translation method (GTM). English is the language of opportunity but young learners residing in remote areas of Himachal Pradesh do not get the environment to learn and speak the language. This paper tries to establish the importance of using NVC and suggests some ways of how NVC can be used in the classroom along with verbal communication (VC) by the teachers which will help to develop English communication skills among primary students in India in general and Himachal Pradesh in particular.